Traditional Chinese Medicine-derived formulations and extracts modulating the PI3K/AKT pathway in Alzheimer’s disease - Ma, Lan; Wang, Jing; Zhou, Rong; Chen, Miao; Huang, Zuxiu; Lin, Shuyang (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is a common neurodegenerative disorder characterized by memory decline, cognitive impairment, and behavioral abnormalities. Pathologically, AD is marked by neurofibrillary tangles caused by excessive phosphorylation of Tau protein and abnormal deposition of β-amyloid (Aβ) in the brain. The PI3K/AKT signaling pathway plays a crucial role in the development, survival, and metabolic regulation of the central nervous system, particularly in neuronal growth, differentiation, and apoptosis. However, this pathway is often inhibited in AD patients.In recent years, studies have shown that herbal formulations and extracts derived from Traditional Chinese Medicine (TCM) can regulate the PI3K/AKT signaling pathway, thereby improving AD pathological models. This study reviews fundamental research on both active metabolites and compound formulations from TCM for the treatment of AD, targeting the PI3K/AKT signaling pathway.Keywords include “Alzheimer’s disease” “AD” “dementia” “PI3K” “AKT” “Traditional Chinese Medicine” “Chinese herbology” “Chinese medicine” and “TCM”.The study is based on relevant literature published over the past 15 years, primarily sourced from electronic databases such as Web of Science, PubMed, CNKI, Wanfang, and VIP databases.The findings indicate that herbal formulations and extracts derived from TCM can mitigate AD pathology by regulating the PI3K/AKT signaling pathway, reducing Tau protein phosphorylation and Aβ deposition, inhibiting inflammatory responses and oxidative stress, and alleviating neuronal apoptosis. This study enhances our understanding of the anti-AD mechanisms of TCM through the PI3K/AKT pathway and offers new insights for the future.